A review on anaerobic biofilm reactors for the treatment of dairy industry wastewater - Karadag, Dogan; Koroglu, Oguz Emre; Ozkaya, Bestami; Cakmakci, Mehmet (ELSEVIER SCI LTD, 2015)
The dairy industry produces significant quantities of wastewater that have a high potential to pollute the environment if it is not properly treated. Dairy wastewater is rich in organic materials along with other pollutants, and anaerobic treatment technologies have been successfully applied due to its high biodegradability. Several research papers have been published on the application of anaerobic biofilm technologies for dairy wastewater under different operational conditions. This paper provides a critical review focusing on biofilm reactors for anaerobic treatment of dairy wastewaters of varying strengths. The effects of organic loading rate and hydraulic retention time on the performance of bioreactors are discussed and operational problems are summarized. Evaluation of reports indicates that biofilm reactors have great performance stability and hybrid bioreactors provide higher organic matter removal and methane production. Among bioreactors, up-flow anaerobic filter packed with varying media has provided higher treatment efficiency and it has higher tolerance against hydraulic shock loadings and heavy metal toxicity. Furthermore, more research should be conducted on low-temperature applications to increase net energy gain from dairy wastewaters. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Dairy wastewater; Anaerobic treatment; Biofilm reactor; Methane yield; FLUIDIZED-BED REACTOR; CHEESE-WHEY; START-UP; METHANE PRODUCTION; BIOGAS PRODUCTION; DIGESTION; PERFORMANCE; BATCH; FILTER; PH; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Engineering